Composition and metabolizable energy of feed used by fallow deer (Dama dama) in a coastal Mediterranean ecosystem - Poli, B M; Focardi, S; Tinelli, A (Small Ruminant Research, 1996)
Data on the impact of a population of about 1000 (spring estimate) fallow deer (Dama &ma) on eight shrubs and mono- and dicotyledonous plants were collecred in a coastal Mediterranean environment from December 1990 to March 1992. Four species of shrubs (Cistus salvifoiius, Phillyrea larifolia, Rubus ulmifolius. Quercus ibex) and mixed graminoids were preferentially consumed. In autumn-winter the acorns of several species, Q. cerris and Q. ilex in particular, were also consumed. We determined the chemical composition, in vivo digestibility coefficients and metabolizable energy content of the feed. On average, R. ulmifolius had the lowest fibre content (18% DM) and the highest protein content (12% DM), organic matter digestibility (59%) and metabolizable energy value (2083 kcal ME kg- ’ DM). C. saluifolius, P. fafifolia and mixed graminoids did not differ significantly in organic matter digestibility (OMD) and nutritive value (I 801, 1765 and 1557 kcal ME kg-’ DM, respectively), while Q. ilex had the lowest nutrient estimates with 32% OMD and 1362 kcal ME kg-’ DM. Forage quality traits usually peaked in spring and autumn. Metabolizable energy was positively correlated with protein, neutral detergent fibre and N-free extractives contents, and negatively correlated with the acid detergent fibre content. Acorns were generally highly digestible; in particular, the seed of Q. farniu and Q. ilex showed 80% and 83% OMD, respectively. In a Mediterranean environment the summer seems the most critical season for fallow deer. The results of this work are important for assessing the carrying capacity of wild Mediterranean ecosystems for fallow deer.
Keywords: digestibility; Fallow deer; Feed quality; in vitro; Mediterranean ecosystems

THE NUTRITIONAL CARRYING-CAPACITY OF 4 MEDITERRANEAN HABITATS FOR FALLOW DEER (DAMA-DAMA) - Focardi, S; Poli, B M; Tinelli, A (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1995)
The assessment of the trophic value of the most consumed feed by fallow deer in a coastal mediterranean landscape (Rubus ulmifolius, Cistus salvifolius, Phyllirea latifolia, Quercus ilex and graminoids) was based on in vitro digestibility trials, performed throughout the year (1 set of samples per season) using rumen inocula from wild fallow deer from the Preserve of Castelporziano, collected simultaneously with the vegetal samples. Moreover, in vivo digestibility coefficients have been estimated by using standard feed (for fallow deer) of known in vivo digestibility. Using the digestibility coefficients, the metabolizable energy yield of studied forage items was computed. Information about plant biomass, structure of fallow deer population, metabolizable energy yields, estimates of forage intake and energy requirements were combined using the model presented by Hobbs and Swift (1985) to evaluate the nutritional carrying capacity of four typical mediterranean habitats (natural evergreen oak wood, scrub mixed plantations of Quercus ilex and Pinus pinea, open pastures). Spring represents the most favourable situation, while summer, autumn and winter exhibit similar values of carrying capacity of about 15-20 deer/100 ha. Mixed plantations of Pinus pinea and Q. ilex seem to be the most productive condition for fallow deer.
APS
Keywords: Cistus salvifolius; digestibility; fallow dear; mediterranean landscape; Phyllirea latifolia; Quercus ilex; Rubus ulmifolius; trophic value